PHYSICAL AND ORGANOLEPTIC QUALITY OF TEMPE SYNBIOTIC ICE CREAM WITH COMPARISION OF THE MOUNT OF PINEAPPLE FERMENTATION RESULT (Ananas Comosus (L) Merr) - Ambar Fidyasari; Sukma Irlanda Firdauzy; Wahyu Maslukah (Jurnal Inovasi Penelitian, 2022)
Abstract By using tempe and pineapple food ingredients, it can increase the selling value of the ingredients and make it one of the new food innovations that can be accepted by the community. Ice Cream Synbiotics are frozen drinks that contain probiotics and prebiotics. Tempe is a traditional food that has been known in Indonesia, made by fermentation orZymosis. The purpose of this study is to determine the physical quality of tempe synbiotic ice cream withcomparison of the amount of fermented pineapple juice. This research is included in the research Experiment with data analysis used is the One Way Anova statistical test. Results that obtained fromphysical quality testing of Overrun, namely, 50 ml: 17.95, 100 ml: 48.73, 150 ml: 1.44,Viscosity 50 ml : 1.7813cp, 100 ml: 730,667cp, 150 ml : 669,667cp, pH 50 ml: 5.0233, 100 ml: 5.0833,150 ml: 5,4100. The results of the organoleptic test of the three treatments had the same color, taste, and smell. Texture organoleptic yield 50 ml: soft, 100 ml: slightly coarse, 150: coarse. Result conclusionanalysis of the physical quality of synbiotic ice cream, the 50 ml treatment was the best treatment in terms of texture and texture the best ANOVA test on viscosity and overrun testing